PENGARUH TEKNIK RELAKSASI TERHADAP ADAPTASI NYERI PERSALINAN IBU BERSALINKALA I FASE AKTIF DI BPS WILAYAH PUSKESMAS PATRANG KABUPATEN JEMBER TAHUN 2012 - Moh. Wildan; Yuniasih Purwaningrum (Fakultas Kesehatan Masyarakat, Universitas Jember, 2013)
In the first stage of labor uterine contractions that cause pain stimuli, approximately 90% of labor is accompanied by pain. Efforts to reduce or eliminate non-pharmacological pain in childbirth with hypnosis, reduce the perception of pain, cutaneous stimulus and Relaxation Techniques. Relaxation techniques are external actions that affect the internal response of the individual. This study aims to determine the effect of relaxation techniques to adaptation of the first stage of labor pain in the active phase of Public health centers in the district Patrang Jember. The research design was pre Experiment (Quasi experiment) by the method of a